Early glaciological and Quaternary Geology cooperation - Zilliacus, Harry (Polar Research Institute of China - PRIC, 2021)
The article depicts the author’s experiences of Glaciology and Quaternary Geology research between Finland and the People’s Republic of China. The focus is on a visit to a glaciological station in Tianshan in 1988. The climate is continental displaying warming-up and increased precipitation since the end of the 1980’s. The data collected here is of utmost importance when analysing the future development of the glaciers. Some associations to the historic Silk Roads are made having implications on the Belt and Road strategy launched by the Chinese. As to problems of sea and lake ice, Finland and the P. R. China have found issues of mutual interest resulting in continuing cooperation in the Arctic and in ice-covered areas of China. New forms of bilateral collaboration such as university education and training have evolved encompassing coming generations.